The Influence of Tax Service Quality, Taxpayer Awareness and Tax Sanctions on Individual Taxpayer Compliance (At the Bandung Bojonagara Pratama Tax Service Office) - Caserio Daur, Fransisko; Kusumawardani, Astrin; Ihsan Muchtar, Muhammad (Dinasti Publisher, 2024)
Indonesia is a country that works hard to improve the lives of its citizens. The government relies mainly on tax income to generate revenue. To collect more taxes, the government uses various strategies. Tax is a mandatory contribution that individuals or companies owe to the state, based on the law, and is utilized for the benefit of the people. The aim of this research is to determine and explain how the quality of tax services, taxpayer knowledge, and tax sanctions affect individual taxpayer compliance in the Bandung Bojonagara Pratama Tax Service Office. The research method used in this study is quantitative, with a descriptive and verification approach, and the sample was purposefully selected. This study collected primary data from the Bandung Bojonagara Pratama Tax Service Office, literature studies, and questionnaires. The population of this study was 293,817, with a sample size of 100 individual taxpayers. The study found that the quality of tax services and taxpayer knowledge have a significant impact on taxpayer compliance in paying individual taxes. However, tax penalties have little influence on taxpayer compliance in paying individual taxes.